A Ubiquitous Learning Approach on Robotics - Mota, Fernanda P.; Kalbermatter, Rebeca B.; Oliveira, Lizandro De S.; Lima, José (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
Ubiquitous learning refers to the integration of learning processes with everyday environments and activities using technology. By leveraging ubiquitous learning principles in the field of robotics, we can foster an immersive and interactive learning environment that promotes continuous learning and knowledge acquisition. This paper presents an in-depth exploration of a ubiquitous learning approach for robotics with the aim to enhance the educational experiences and capabilities of robotic systems. Furthermore, it explores the potential benefits and challenges of ubiquitous learning in the field of robotics, such as increased adaptability, personalized learning experiences, and the development of lifelong learning skills. The results indicate that a ubiquitous learning approach can significantly enhance the learning capabilities of students.